Stiffing the creditor: Asset verifiability and bankruptcy - Giambona, Erasmo; Lopez-de-Silanes, Florencio; Matta, Rafael (Journal of Financial Intermediation, 2022)
Evidence suggests that asset pledgeability, debt complexity, and control rights of dispersed debt influence financial distress resolution. We model how courts’ imperfect verifiability of assets and valuable control of misaligned creditors shape firms’ debt structure and create coordination problems that determine distress outcomes and financing. A key result is that an increase in verifiability allows financially constrained firms to fund projects by pledging more assets to misaligned creditors, making contract renegotiation in distress times more difficult and increasing the probability of bankruptcy. Since equity receives less in the event of distress, constrained firms choose riskier projects with higher returns. Consistent with our model, bankruptcy filings increase after the U.S. Supreme Court decision imposing a “market test” to assess the value of stockholders’ interest in debtor proposals. The effect is stronger for firms with low asset verifiability. These firms also experienced an increase in recovery rates, debt capacity, and risk-taking. Our findings suggest that reforms improving the verifiability of assets substantially impact credit access. However, our results also point out that improving asset verifiability may be insufficient for constrained firms with aligned creditors. Therefore, complementary reforms that facilitate firms’ access to creditors from different market segments may be necessary.